Impact of Diﬀerent Physiotherapy Programs on Balance and Gait in Patients with Cerebral Infarction - Paula Smailytė; Eglė Lendraitienė; Ieva Žemaitienė (Lithuanian Sports University, 2023)
Background. An ischemic stroke has long-term adverse effects on the physical, emotional, and social well-being of the stroke survivor, so it is very important to help the patient regain independence and lost functions as quickly and efficiently as possible. Dynamic Neuromuscular Stability exercises can restore movement patterns in these patients by simulating central nervous system. The aim. To compare the effects of conventional physiotherapy and dynamic neuromuscular stabilization integrated into conventional physiotherapy on balance and gait in patients with cerebral infarction. Methods. The study included 30 subjects who survived an ischemic stroke. Subjects were randomly divided into two groups of 15 people in each for different interventions: Conventional physiotherapy and Conventional physiotherapy combined with integrated dynamic neuromuscular stabilization. Subjects were examined at a baseline and after the interventions. Patients' balance was assessed using the Biodex platform, which was chosen to evaluate fall risk, trunk stability, stability limits and sensory organization. Gait parameters (step length and step width) of the affected and unaffected leg were assessed using the Zebris FDM-T treadmill. Results. Both conventional physiotherapy and physiotherapy with integrated dynamic neuromuscular stabilization improved gait parameters of the patients, as well as improving the results of the tests of fall risk, postural stability, stability limits, and the results of the sensory integration test when testing with eyes open on a stable surface (p<0.05). However, the results of the sensory integration tests while standing on a stable surface with eyes closed (p<0.001), with eyes open on an unstable surface (p<0.001) and with eyes closed on an unstable surface (p=0.021) improved only post physiotherapy with integrated dynamic neuromuscular stabilization. Conclusions. Both conventional physiotherapy and physiotherapy with integrated dynamic neuromuscular stabilization significantly improved gait and balance parameters in stroke patients.  Keywords: Dynamic neuromuscular stabilization, stroke, balance, trunk stability, gait.